Outcome of Esophageal Variceal Ligation in Cirrhotic Patients: Experience in a Tertiary Care Hospital in Dhaka (BIRDEM Medical Journal, 2019)
Background: Bleeding from esophageal varices in cirrhosis is an emergency condition. Esophageal varices band ligation has shown better results in terms of variceal obliteration as well as having fewer side effects like ulceration, perforation and stricture formation.Methods: This observational study was conducted at the gastroenterology department of BIRDEM general hospital, from September 2014 to March 2015. Subjects were eligible if they had a diagnosis of cirrhosis based on history, physical examination, biochemical parameters and presence of esophageal varices in upper gastrointestinal endoscopy. All patients were tested to determine the cause of liver cirrhosis. All patients under-went upper gastrointestinal endoscopy after consent. Esophageal variceal ligation was done at appropriate situation and patients were followed up later on. SPSS 23 was used for statistical analysis.Results: The sample size was 69. The cumulative mean age was 55.58±14.462 years (range: 20-90), with gender-based mean age of 54.76±15.704 years for males and 57.22±11.739 years for female. Mild portal hypertensive gastropathy (PHG) was found 31 (44.9%) patient and severe PHG 36 (52.2%). Patients were followed up for mean period of 8.52±3.6 months. Variceal obliteration was achieved in 25 (36.2%) patients, while 06 (8.7%) cases developed re-bleeding during the study period and this type of patients were managed by other modalities or combination therapies. Recurrence of varices occurred in 13 (18.8%). 25 (36.2%) patients reduction of varix size occured after esophageal variceal ligation (EVL), 32 (46.4%) required second session and 12 (17.4%) required more than second session (Table-2). Thirty nine (56.5%) patients experienced minor adverse events like GI discomfort (retrosternal pain or dysphagia), while severe adverse events were noticed in 13 (18.8%) patients. Fundal varix was found among 8 (11.6%) patient on follow up endoscopy and GAVE found in 6 (8.69%) patients. All patient developed PHG during follow up endoscopy.Conclusion: Band ligation eradicates esophageal varices with less complications and a lower re-bleeding rate, but at the same time eradication is associated with more frequent development of PHG and fundal varices.Birdem Med J 2019; 9(1): 63-69